2014
DOI: 10.1021/ef500254n
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Initial Stage of Ash Deposition during Oxy-Fuel Combustion in a Bench-Scale Fluidized Bed Combustor with Limestone Addition

Abstract: The technology of oxy-fuel combustion in a circulating fluidized bed boiler is one of the advanced technologies for carbon capture and storage; however, operating problems related to ash deposition are worth investigating. When limestone is added as a sorbent during oxy-fuel combustion, excess CaO particles in the fly ash deposit on heating surfaces and react with high concentrations of CO 2 in the flue gas. These carbonation reactions lead to structural change and formation of bonded deposits. Therefore, depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, there were no significant differences observed in the chemical compositions of the fly ash, and ash deposits between studied combustion atmospheres. Furthermore, Wang et al used the same bench scale FBC facility to assess ash deposition characteristics with limestone under oxy‐fuel combustion conditions, where it was observed that the deposition propensity was higher for oxy‐combustion than for air combustion. This was attributed to physical changes in the particle size distributions rather than in the chemical composition of the fly ash.…”
Section: Design and Operational Issuesmentioning
confidence: 99%
“…However, there were no significant differences observed in the chemical compositions of the fly ash, and ash deposits between studied combustion atmospheres. Furthermore, Wang et al used the same bench scale FBC facility to assess ash deposition characteristics with limestone under oxy‐fuel combustion conditions, where it was observed that the deposition propensity was higher for oxy‐combustion than for air combustion. This was attributed to physical changes in the particle size distributions rather than in the chemical composition of the fly ash.…”
Section: Design and Operational Issuesmentioning
confidence: 99%
“…The details about controlling probe surface temperature can be found in Refs. and . The temperature controlling system is the same as that of the previous ash deposit probe.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…However, no remarkable differences were observed in the chemical compositions of the ash deposits and fly ash between different combustion modes. By using the same anthracite, the effects of limestone addition on ash deposition behavior were explored. , The results showed that, in the absence of limestone, the ash deposition rate did not change significantly when switching from air to 30% O 2 /70% CO 2 combustion. It was different from the observation in the previous work, where 30% O 2 /70% CO 2 combustion led to a significantly higher ash deposition rate.…”
Section: Ash Formation and Deposition In Oxy-fbcmentioning
confidence: 99%